A 24-Year Narrative Review of an Early Intervention for Psychosis Service in Hong Kong - Eric Chen (BJPsych Open, 2025)
Aims: Early intervention for psychosis (EIP) programmes are specifically designed mental health initiatives aimed at the early identification and optimal management of the initial stages of psychotic disorders. The successful launch, development and consolidation of EIP programmes typically span decades and involve many factors. While quantitative meta-analytic studies have assessed the overall efficacy of EIP programmes, there remains a need for more nuanced evaluations that delve into less quantifiable processes. Such detailed accounts are crucial for facilitating the optimisation of similar programmes, especially in settings with limited resources, but they are rarely available. This study provides a comprehensive account of the development and optimisation of an early intervention programme in Hong Kong over 24 years, offering pertinent insights particularly for low- to middle-resource mental health environments.